PROBLEMS OF RELIABILITY OF HARDWARES IN COMPUTER-AIDED SYSTEMS OF TECHNOLOGICAL PROCESSES CONTROL - Orikhovskyy , Roman (Forestry, Forest, Paper and Woodworking Industry, 2024)
The questions of application of modern methods of determination of reliability of automated control the system technological processes are examined for the decision of tasks of increase efficiency of functioning of the automated production systems on the enterprises of industrial forestry complex. Influence of reliability of equipment on the actual productivity of the automated production systems is probed. Diminishing of reliability of equipment results in the considerable decline of the actual productivity of the automated production systems and decline of stability of technological operations. It is expedient to conduct the increase of reliability of the automated production systems by the structural backuping, development of charts of arrangement of equipment, structurally self-reactance optimization, imitation design.